Penambahan Kombinasi Ekstrak Etanol dan Etil Asetat Tepung Rumput Laut Kappaphycus alvarezii pada Pakan Komersil Ikan Nila (Oreochromis niloticus) - Metamelya, Baiq Areta; Yuniarti Lumbessy, Salnida; Abidin, Zaenal (Pena Akuatika : Jurnal Ilmiah Perikanan dan Kelautan, 2025)
This study was conducted to determine the effect of adding a combination of ethyl acetate + ethanol extract of K. alvarezii seaweed to commercial diets on growth and survival of tilapia (O. niloticus). The research was conducted from June-October 2023 at the Production and Reproduction Laboratory of Mataram University. The method used was an experimental method consisting of 4 treatments with 3 replications, namely the control treatment without the addition of extracts (P1), feed with the addition of a combination of ethyl acetate + ethanol extract of K. alvarezii 1:3 (P2), a combination of ethyl acetate + ethanol extract of K. alvarezii 1:4 (P3) and a combination of ethyl acetate + ethanol extract of K. alvarezii 1:5 (P4). The extraction was carried out by maceration at room temperature for 30 h, followed by evaporation. The evaporated extract was added to the diet at a dose of 2 g/kg diet. The parameters tested were absolute length, absolute weight, specific growth rate, feed utilisation efficiency, feed conversion ratio, survival rate and water quality. The data obtained were analysed by ANOVA test and Duncan's further test. The results showed that the combination treatment of ethyl acetate extract and ethanol meal of K. alvarezii 1:5 (P4) could increase the absolute weight and better feed utilisation efficiency. While the combination treatment of ethyl acetate extract and ethanol of K. alvarezii flour 1:4 (P3) and 1:5 (P4) provides the same ability to increase LPS and FCR of tilapia